Photocatalytic mineralization of diisopropanolamine (DIPA) from natural gas industry wastewater under visible light irradiation: Response surface optimization of synthesis parameters - Nadia Riaz; Muhammad Saqib Khan; Sami Ullah; Abulhassan Ali; Mohamad Azmi Bustam; Asaad Khalid; Tensangmu Lama Tamang; Ajmal Khan; Ahmed Al-Harrasi (Results in Engineering, 2024)
The photocatalytic mineralization of diiospropanolamin (DIPA) in aqueous solution was investigated employing modified TiO2 under visible light. Response surface methodology based central composite design (CCD) was used to explore the effect of different synthesis parameters. The analysis showed substantial impact (p < 0.0195) of operational factors and their interactions on DIPA mineralization during photocatalytic degradation. Model predictions closely aligned with experimental outcomes (R2 = 0.9706, Adj-R2 = 0.9442). The morphology analysis revealed spherical agglomerates with well-dispersed iron on TiO2, which was corroborated by Raman spectroscopy showing similar spectra to bare TiO2 however, increased intensity and broader peaks at higher iron concentrations. Additionally, X-ray Diffraction confirmed the crystalline nature of the synthesized nanocomposite, while BET surface area analysis demonstrated an increasing trend with metal loading. Under optimal conditions, with 5% Fe loading and 300 °C calcination for 1 h, the photocatalytic efficiency significantly improved, achieving 45.78% DIPA mineralization in the first hour and complete (100%) mineralization in 2 h. This represents a promising solution for addressing natural gas industry wastewater challenges. Future goals include further optimization for enhanced efficiency.